Proses Eksanguinasi dan Kualitas Fisik Daging Sapi Brahman Cross dengan Waktu Istirahat Berbeda Sebelum Pemotongan - Adhyatma, M.; Nuarini, N.; Yani, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The aim of this study was to examine blood parameters during exsanguination process, and physical meat quality characteristics of Brahman cross at different preslaughter resting periods. The total number of cattle used in this study was 24 heads of Brahman cross; they were alloted to  3, 6, 12 and 24 hours preslaughter resting periods with 6 heads replication for each treatment. The measurements of blood parameters comprised  gushing blood downtime, weight and presentage of blood loss. Physical characteristics of Meat quality assessment were based on ultimate pH, water holding capacity, cooking loss, and shear force. The data was analyzed using analysis of variance and further differences between treatments were tested using Duncan’s multiple range test. The results showed that preslaughter resting period had significant effected (P<0.05) on gushing blood downtime, and the weight and presentage of blood loss.  Cattle with 24 hours preslaughter resting periods had longer gushing blood downtime, higher  weight and presentage of blood loss, and they yielded meat with lower ultimate pH, cooking loss and shear force value if compared to those with 3 and or 6 hours preslaughter resting period.  Thus, increasing cattle resting periods before slaughter from 3 to 24 hours  might have increased gushing blood downtime, blood lost at exsanguination and cosequently  produced better meat quality.